2011
DOI: 10.3324/haematol.2011.046466
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-mediated Mcl-1 and survivin downregulation restores TRAIL-induced apoptosis in non-Hodgkin's lymphoma B cells

Abstract: The online version of this article has a Supplementary Appendix. BackgroundNon-Hodgkin's B-cell lymphomas account for approximately 70% of B-cell lymphomas. While its incidence is dramatically increasing worldwide, the disease is still associated with high morbidity due to ineffectiveness of conventional therapies, creating an urgent need for novel therapeutic approaches. Unconventional compounds, including polyphenols and the cytokine TRAIL, are being extensively studied for their capacity to restore apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 41 publications
6
51
0
Order By: Relevance
“…6,7 In this context, current therapeutic approaches aim at combining TRAIL with conventional chemotherapy or targeted therapies to circumvent different resistances to TRAIL-induced apoptosis due to the presence of the antagonist receptors TRAIL-R3 (DcR1) and TRAIL-R4 (DcR2),the caspase-8 inhibitor c-FLIPor to a defect in the mitochondrial pathway. [8][9][10] Alternatively, mutagenesisor multimerization of TRAIL (or TRAIL derivatives)to mimic native membrane-bound TRAIL are explored to increase TRAIL efficacy. While 88 ng/mL TRAIL was required to kill 50 % of H1703 cells, the IC50 was reached with only8 ng/mL NPT, demonstrating that NPT action was largely superior than TRAIL one in inducing apoptosis of these cells.…”
mentioning
confidence: 99%
“…6,7 In this context, current therapeutic approaches aim at combining TRAIL with conventional chemotherapy or targeted therapies to circumvent different resistances to TRAIL-induced apoptosis due to the presence of the antagonist receptors TRAIL-R3 (DcR1) and TRAIL-R4 (DcR2),the caspase-8 inhibitor c-FLIPor to a defect in the mitochondrial pathway. [8][9][10] Alternatively, mutagenesisor multimerization of TRAIL (or TRAIL derivatives)to mimic native membrane-bound TRAIL are explored to increase TRAIL efficacy. While 88 ng/mL TRAIL was required to kill 50 % of H1703 cells, the IC50 was reached with only8 ng/mL NPT, demonstrating that NPT action was largely superior than TRAIL one in inducing apoptosis of these cells.…”
mentioning
confidence: 99%
“…Our results were similar to the previously published data that demonstrated the resistance of C. albicans to 60 g/ml FCZ (3). The sensitization of human cancer cells by QC has been studied well in various carcinoma cell lines (36)(37)(38), but the sensitization of human fungal pathogens by QC has not been investigated. Upon combined treatment with QC and FCZ, NBC099 cells showed strongly en- …”
Section: Discussionmentioning
confidence: 99%
“…We then demonstrated that celecoxib potentiated TRAIL-induced apoptosis in lymphoma B cells, including TRAIL-resistant B-cell lines like RAJI and RL, which are much more resistant to cell death (ref. 32; Fig. 2A).…”
Section: Celecoxib Acts On B Cells Through Cox-2-independent Effects mentioning
confidence: 99%